PENGARUH FEE AUDIT DAN KOMPETENSI AUDITOR TERHADAP MOTIVASI AUDITOR PADA KANTOR AKUNTAN PUBLIK DI KOTA PADANG - Dewi Zulvia; Era Gustilia (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study to provide empirical evidence of the effect of audit risk, auditor experience and professionalism on the consideration of the level of materiality at the Public Accounting Firm in the city of Padang. The population in this study are all public accoounting firms in the city of Padang. Purposive sampling technique is the sampling technique used in this study. The sample in this study were all senior auditors and junior auditors at the Public Accounting Firm Padang. This type of research is quantitative research. Multiple linear regression analysis was used in this study the audit Fee was positive and had a significant effect on auditor motivasion, which was indicated by a significant value of 0,000 <0,05, and auditor competence have a positive and significan effectt on auditor motivasion. Level indiated by a significant value of 0,000 <0,05